The Impact of Public Policies on Teaching Learning Activities Due to The Covid-19 Pandemic - Ni Luh Putu Lasmin Maharani; Ni Nyoman Diah Utari Dewi; Ida Ayu Putu Sri Widnyani; Luh Riniti Rahayu; Anak Agung Gede Rai (Journal of Communication in Scientific Inquiry (JCSI), 2024)
Covid-19 In response to the COVID-19 pandemic, Indonesia, as declared a national disaster by President Joko Widodo through Presidential Decree No. 12 of 2020, has transitioned into an emergency response phase for non-natural disasters. The World Health Organization labeled COVID-19 a global pandemic on March 11, 2020. The pandemic has significantly disrupted various aspects of daily life, notably the education sector. To maintain educational continuity amidst this crisis, the Indonesian government implemented online learning policies. This shift from traditional face-to-face instruction to distance education poses unique challenges, especially for elementary and kindergarten students. This journal explores the impact of these public policies on teaching and learning during the pandemic, using a descriptive-analytical literature review. Findings reveal that while technology facilitates continued education, it also introduces challenges related to academic culture, values, attitudes, skills, and technological readiness. The study underscores the crucial role of technology in bridging the gap created by the pandemic and highlights the need for addressing associated obstacles to enhance the effectiveness of online education.